NEW ASPECTS OF PATHOLOGY AND NORMS OF MATRIX METALLOPROTEINASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The first discovered activity of MMPs was their ability to hydrolyze extracellular matrix proteins. The expression of MMPs in a wide range of cells and tissues ensures their participation in a variety of physiological processes. Neutrophils, monocytes, macrophages, lymphocytes, mast cells, fibroblasts, osteoclasts, chondrocytes, keratinocytes, endothelial, epithelial and smooth muscle cells, as well as cells of various tumors are capable of producing MMPs. Degradation of extracellular matrix components ensures tissue remodeling, maintaining its architecture and homeostasis, and also frees up space for cell migration, which is especially important for embryogenesis, embryo implantation, growth and development, angiogenesis, and wound healing.